PENGARUH PENAMBAHAN RESORSINOL PADA PEMBUATAN PEREKAT LIKUIDA SABUT KELAPA - Mutiara Istiqomah; Netti Herlina (Jurnal Teknik Kimia USU, 2014)
Liquid adhesive coconut coir is the result of a reaction between lignin powder material used with aromatic compounds at high temperatures in order to obtain a solution that can be used as an adhesive. This study aims to investigate the characteristics of liquid adhesive of coconut coir (LACC) qualities and determine the effect of resorcinol in the manufacture of adhesives LACC. The study was conducted in three phases: the first stage of coir manufacturing particles, which at this stage coir made into particles of 100 mesh, adhesive manufacturing second stage LACC which at this stage there are two stages of the liquefaction reaction coir and polymerization, and the third stage addition of resorcinol LACC into the adhesive. The variables used in this study is the addition of variable rate resorcinol at 10, 20, 30% by weight. Variables - variables that were analyzed pH, viscosity, spesific gravity, solid content, formaldehyde-free rate and compound analysis using FT-IR adhesive LACC to conditions without the addition of resorcinol and with the addition of 30% resorcinol. The results showed that the addition of resorcinol LACC influence on the resulting adhesive, which has a liquid form, the pH ranged from 12.6 to 10.6, 43,867- 131.712 cps viscosity, specific gravity of 1.252 to 1.258, solid content 46.67 to 80%, from 1.952 to 1.051% formaldehyde content. FT-IR results showed similarity LACC adhesive force phenol formaldehyde resin, namely the presence of the OH group, C = H of the aromatic ring, of methylene CH, CO from ether and fenolic compound.